SOME ASPECTS OF THE LISINOPRIL USAGE IN ARTERIAL HYPERTENSION TREATMENT - N. A. Jaiani (Рациональная фармакотерапия в кардиологии)
The evidence basis and advantages of the lisinopril usage in a clinical practice as antihypertensive drug are presented. Special attention is paid to organoprotective lisinopril effects and lisinopril implementation at special clinical conditions (chronic obstructive pulmonary disease comorbidity, elderly patients, and concomitant liver diseases). Pharmacoeconomic aspects of lisinopril usage in arterial hypertension are also considered.